Properties and Derivatives of Cyclic Sulphur Imides - Tingle, Edith May (My University, 1968)
The methylation of three isomeric hexasulphur diimides under basic conditions has been investigated. Both mono- and dimethylated products have been obtained from the 1, 5- and 1,4-hexasulphur diimides. The anion formed from the 1,3 isomer was found to undergo decomposition, the major products being polysulphides and N-methyl heptasulphur imide. The usefulness of proton NMR, mass spectra, and infrared spectra in conjunction with these compounds has been considered.
Keywords: properties, derivatives, cyclic, sulphur, imides